Lipopolysaccharide induces up-regulation of TGF-α through HDAC2 in a rat model of bronchopulmonary dysplasia. - Wensi Ni (Public Library of Science (PLoS), 2014)
Bronchopulmonary dysplasia (BPD) is characterized by alveolar simplification with decreased alveolar number and increased airspace. Previous studies suggested that transforming growth factor-α (TGF-α) may contribute to arrested alveolar development in BPD. Histone deacetylases (HDACs) control cellular signaling and gene expression. HDAC2 is crucial for suppression of inflammatory gene expression. Here we investigated whether HDAC2 was involved in the arrest of alveolarization, as well as the ability of HDAC2 to regulate TGF-α expression in a rat model of BPD induced by intra-amniotic injection of lipopolysaccharide (LPS). Results showed that LPS exposure led to a suppression of both HDAC1 and HDAC2 expression and activity, induced TGF-α expression, and disrupted alveolar morphology. Mechanistic studies showed that overexpression of HDAC2, but not HDAC1, suppressed LPS-induced TGF-α expression. Moreover, the HDAC inhibitor TSA or downregulation of HDAC2 by siRNA both significantly increased TGF-α expression in cultured myofibroblasts. Finally, preservation of HDAC activity by theophylline treatment improved alveolar development and attenuated TGF-α release. Together, these findings indicate that attenuation of TGF-α-mediated effects in the lung by enhancing HDAC2 may have a therapeutic effect on treating BPD.